Thyroid hormone modulation during zebrafish development recapitulates evolved diversity in danionin jaw protrusion mechanics. Issue 5 (2nd August 2019) - Galindo, Demi; Sweet, Elly; DeLeon, Zoey; Wagner, Mitchel; DeLeon, Adrian; Carter, Casey; McMenamin, Sarah K.; Cooper, W. James
Abstract : Protrusile jaws are a highly useful innovation that has been linked to extensive diversification in fish feeding ecology. Jaw protrusion can enhance the performance of multiple functions, such as suction production and capturing elusive prey. Identifying the developmental factors that alter protrusion ability will improve our understanding of fish diversification. In the zebrafish protrusion arises postmetamorphosis. Fish metamorphosis typically includes significant changes in trophic morphology, accompanies a shift in feeding niche and coincides with increased thyroid hormone production. We tested whether thyroid hormone affects the development of zebrafish feeding mechanics. We found that it affected all developmental stages examined, but that effects were most pronounced after metamorphosis. Thyroid hormone levels affected the development of jaw morphology, feeding mechanics, shape variation, and cranial ossification. Adult zebrafish utilize protrusile jaws, but an absence of thyroid hormone impaired development of the premaxillary bone, which is critical to jaw protrusion. Premaxillae from early juvenile zebrafish and hypothyroid adult zebrafish resemble those from adults in the genera Danionella, Devario, and Microdevario that show little to no jaw protrusion. Our findings suggest that evolutionary changes in how the developing skulls of danionin minnows respond to thyroid hormone may have promoted diversification into different feeding niches. Abstract : Thyroid hormone and the evo‐devo of fish jaw protrusion. (a) The ascending arm (red bracket) of the premaxillary bone (pink) allows jaw protrusion in feeding zebrafish. (b) Evolutionary and developmental variation in ascending arm length in the zebrafish and its close relatives. (c) An adult zebrafish that cannot produce thyroid hormone retains a juvenile, non‐protrusile premaxillary shape. HIGHLIGHTS: Jaw protrusion ability affects fish diet. Zebrafish use protrusile jaws. If they develop without thyroid hormone they feed like closely related nonprotrusile fishes. Changes in thyroid hormone signaling may have shaped the evolution of fish feeding.